2007
DOI: 10.1007/s10265-007-0133-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome analysis and its significance in four unicellular algae, Cyanidioshyzon merolae, Ostreococcus tauri, Chlamydomonas reinhardtii, and Thalassiosira pseudonana

Abstract: Algae play a more important role than land plants in the maintenance of the global environment and productivity. Progress in genome analyses of these organisms means that we can now obtain information on algal genomes, global annotation and gene expression. The full genome information for several algae has already been analyzed. Whole genomes of the red alga Cyanidioschyzon [corrected] merolae, the green algae Ostreococcus tauri and Chlamydomonas reinhardtii, and the diatom Thalassiosira pseudonana have been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 92 publications
1
16
0
Order By: Relevance
“…Homology search in the available genomic databases revealed that such bi-domain GPDHs only exist in green alga, but not in higher plants or other species, such as yeasts and animals. Green algae live in diverse and variable environments and can acclimate to different environmental stresses (Osami et al 2008). Analysis of green algae genomes revealed interesting features of gene amplification and diversification, which pointed toward novel mechanisms for survival in the diverse and fluctuating environments (Merchant et al 2007;Graham 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Homology search in the available genomic databases revealed that such bi-domain GPDHs only exist in green alga, but not in higher plants or other species, such as yeasts and animals. Green algae live in diverse and variable environments and can acclimate to different environmental stresses (Osami et al 2008). Analysis of green algae genomes revealed interesting features of gene amplification and diversification, which pointed toward novel mechanisms for survival in the diverse and fluctuating environments (Merchant et al 2007;Graham 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, however, this is unlikely to remove the green genes altogether or to reduce the number significantly, as the C. merolae genome appears to have retained most of the genes shared by red algae and chromalveolates; even including sequences from P. cruentum and C. tuberculosum, only approximately 750 candidate red genes are identifiable from chromalveolates (19). Furthermore, while the C. merolae genome is extremely reduced, it contains greater proportions of some genes, e.g., those involved in translation, DNA replication, and protein and amino acid biosynthesis, than other sequenced photosynthetic eukaryotes (73,78), yet we could visually identify a consistently green signal even in these relatively unreduced functional gene families across both species (Table 1). We consider that even in a most extreme scenario, a consistent and strong green signal should still emerge.…”
Section: Going Green-evidence For Ancient Green Ancestorsmentioning
confidence: 99%
“…This organism belongs to the Prasi-nophyceae class (12), potentially the most ancient species in the green lineage that diverged from the ancestor of all green plants and algae (13)(14)(15). O. tauri has a single starch granule and the full set of genes present in higher plants for polysaccharide metabolism (16).…”
mentioning
confidence: 99%